El aprendizaje cooperativo como método de enseñanza -aprendizaje del voleibol en el bloque de prácticas deportivas en los alumnos de 9no año paralelo “f” de la sección matutina, de educación general básica de la unidad educativa del milenio “Bernardo Valdivieso” de la ciudad de Loja, periodo 2018-2019 - Ruiz Cueva, Edison Harry (2020)
The present investigation entitled; COOPERATIVE LEARNING AS A METHOD OF TEACHING - LEARNING VOLLEYBALL IN THE SPORTS PRACTICE BLOCK IN THE 9TH PARALLEL YEAR “F” OF THE MORNING SECTION, BASIC GENERAL EDUCATION UNIT OF THE MILLENNIUM EDUCATIONAL UNIT "BERNARDO VALDIVIESO" OF THE CITY OF LOJA, PERIOD 2018-2019, whose problem was raised in; How does cooperative learning as a method of teaching-learning of volleyball affect the block of sports practices in the students of the 9th parallel year “F” of the morning section, of General Basic Education of the Educational Unit of the Millennium "Bernardo Valdivieso" of the city of Loja, period 2018-2019?, the main objective is to determine the incidence of cooperative learning as a method of teaching-learning of volleyball, from this the work was proposed through three categories which are; teaching-learning, cooperative learning and volleyball, the methodology of the research has a qualitative-quantitative approach, the type of research is descriptive and with a pre-experimental design. During the process the methods were applied; scientific, descriptive, inductive and statistical observation, techniques such as observation and survey, instruments such as the questionnaire to know the teaching-learning process of the basics of volleyball and a descriptive scale to know the mastery of the basics of volleyball at the beginning and end; by applying the proposal using the cooperative learning method, 100% of the students improved their mastery of the fundamentals; concluding that working the technical fundamentals of volleyball with the cooperative learning method allowed the students to improve their mastery of the fundamentals, the application of the volleyball teaching-learning program using the cooperative learning method is recommended.